Sustainable Building Design: A Brief Review - Rahman, Md Motiar; Haji Juffle, Nor Aqilah; Asli, Rajul Adli (Journal of Advanced Research Design, 2025)
Buildings are liable for the highest global energy consumption and CO2 emission. Wider adoption of sustainable design in buildings can significantly reduce such energy consumption and CO2 emission, along with contributing to a healthier environment, cost savings from reduced energy use, and enhanced occupant comfort. Also, the combination of active and passive design strategies is more effective in reducing energy consumption and CO2 emissions. In this regard, and as the beginning of a recently launched wider study on adopting passive design strategies in buildings, this paper presents a brief and summarized outcomes of the initial literature review. The target is to allow a better understanding of sustainable design practices and extract various active and passive design strategies/features. A total of 59 design strategies have been identified: eight active strategies, 18 passive strategies for lighting and 33 passive strategies for heating, cooling and ventilation purposes. Such strategies/features include: solar panels, shading devices, roof garden and wind towers. These do not use any externally supplied energy, but improve building energy profile. The strategies will be further refined/adjusted for a questionnaire survey to identify their degree of actual practice in building design, which will be feeding into the wider study of adopting passive design strategies. The findings provide a reference for construction professionals and practitioners, pave the route for further academic research, and allow policy makers further insights.